The Effect of Sustainability Report Disclosure and Leverage on Company Value with Environmental Performance as a Moderating Variable (case study of food and beverage sector manufacturing companies listed on the idx for the 2021-2023 period) - agusthin, Yeffi Dwi; Astriani, Devi; Fatihah, Dhea Imroatul (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This study examines the impact of sustainability report disclosure and leverage on firm value with environmental performance as a moderating variable. Using a sample of 33 food and beverage manufacturing companies listed on the IDX in 2021-2023. The background of this study is based on the increasing attention of investors to the sustainability aspects and financial risks of companies, especially in sectors that have a direct impact on the environment and society. Data were obtained through purposive sampling and analyzed using moderated regression (MRA) with the help of SPSS 27. The results of the analysis indicate that sustainability report disclosure has an effect on firm value, while leverage has no effect. Environmental performance is able to moderate the relationship. This study emphasizes the importance of integration between sustainability reporting disclosure, leverage and environmental performance in increasing the perception and value of companies in the eyes of investors.